A Limited Role for Mediodorsal Thalamus in Devaluation Tasks. - Pickens, Charles L. (Behavioral Neuroscience, 2008)
Six experiments were performed to determine the role of mediodorsal thalamus (MD) in the devaluation task, varying the type of contingencies (Pavlovian or operant), the number of reinforcers (one vs. two), and the order of experiments (in naive or experimentally experienced rats). MD-lesioned rats were impaired in devaluation performance when switched between Pavlovian and operant devaluation tasks, but not when switched from one Pavlovian devaluation task to another Pavlovian devaluation task. MD lesions caused no devaluation impairment in a multiple-reinforcer Pavlovian devaluation task. These results suggest that MD lesions impair performance in devaluation tasks as a result of an inability to switch the form of associations made from one type of outcome-encoding association to another. This is in accord with previous literature suggesting that MD is needed for strategy set shifting. The results further suggest that MD is a necessary part of devaluation circuits only in cases in which previous associations need to be suppressed in order for new associations to be learned and control behavior, and otherwise the devaluation circuit does not require MD. Reprinted by permission of the publisher.